PENGARUH FINANCIAL STRESS, SOCIAL INFLUENCE, DAN DIGITAL FINANCIAL LITERACY TERHADAP FINANCIAL MANAGEMENT BEHAVIOR - Salsabila Shafiyah Rihab; Erika Takidah; Susi Indriani (Taksasila Edukasi Insani, 2026)
This research examines the determinants influencing financial management behavior among students of the Faculty of Economics and Business at Universitas Negeri Jakarta (FEB UNJ), particularly in relation to financial stress, social influence, and digital financial literacy. The study adopted a quantitative method with a causal-associative approach. Using the Slovin formula and proportionate random sampling, 251 respondents were selected from 721 students of the 2022 cohort. Primary data were obtained through questionnaires administered online via Google Forms with a five-point Likert scale. The collected data were then processed through multiple regression analysis using SPSS version 31. The findings indicate that financial stress tends to negatively influence financial management behavior, while social influence and digital financial literacy contribute positively and significantly. In addition, all examined determinants simultaneously affect students’ financial management behavior.Keywords : Financial Stress, Social Influence, Digital Financial Literacy, Financial Management Behavior.